The SNABB ADHD treatment scale—An easy-to-use scale on treatment monitoring in childhood ADHD: A pilot study - Nylander, Elin; Hermansson, Jonas; Nygren, Gudrun (Frontiers in Child and Adolescent Psychiatry, 2023)
Information from parents and teachers are essential in the treatment monitoring of children with ADHD. Rating scales are infrequently used in the treatment monitoring, and clinicians are signalling logistic barriers in the administration of rating scales in clinical settings. Here, we aimed to try out a new easy-to-use scale to facilitate information sharing between parents, teachers, and medical staff, in the treatment of childhood ADHD. We examined the SNABB scale in a clinical sample of 27 child- and adolescent patients with any type of ADHD, in a routine clinical setting. We compared the outcome of the new SNABB scale with the commonly used SNAP-IV. The SNABB questions concerning ADHD cardinal symptoms hyperactivity and impulsivity were associated with the concurrent SNAP-IV subscale, with moderate to strong correlations. The SNABB inattention question failed all associations with the concurrent SNAP-IV inattention subscale. A secondary finding was that the SNABB mood regulation question correlated with the SNAP-IV ODD-subscale at all three measure points. Present pilot study brings promising results for the possibility to carry out larger scale studies concerning the psychometric properties of the SNABB scale.